Time to Stabilization of Anterior Cruciate Ligament–Reconstructed Versus Healthy Knees in National Collegiate Athletic Association Division I Female Athletes - Webster, Kathryn A. (The National Athletic Trainers' Association, Inc, 2010)
CONTEXT: Jump landing is a common activity in collegiate activities, such as women's basketball, volleyball, and soccer, and is a common mechanism for anterior cruciate ligament (ACL) injury. It is important to better understand how athletes returning to competition after ACL reconstruction are able to maintain dynamic postural control during a jump landing. OBJECTIVE: To use time to stabilization (TTS) to measure differences in dynamic postural control during jump landing in ACL-reconstructed (ACLR) knees compared with healthy knees among National Collegiate Athletic Association Division I female athletes. DESIGN: Case-control study. SETTING: University athletic training research laboratory. PATIENTS OR OTHER PARTICIPANTS: Twenty-four Division I female basketball, volleyball, and soccer players volunteered and were assigned to the healthy control group (n  =  12) or the ACLR knee group (n  =  12). Participants with ACLR knees were matched to participants with healthy knees by sport and by similar age, height, and mass. INTERVENTION(S): At 1 session, participants performed a single-leg landing task for both limbs. They were instructed to stabilize as quickly as possible in a single-limb stance and remain as motionless as possible for 10 seconds. MAIN OUTCOME MEASURE(S): The anterior-posterior TTS and medial-lateral TTS ground reaction force data were used to calculate resultant vector of the TTS (RVTTS) during a jump landing. A 1-way analysis of variance was used to determine group differences on RVTTS. The means and SDs from the participants' 10 trials in each leg were used for the analyses. RESULTS: The ACLR group (2.01 ± 0.15 seconds, 95% confidence interval [CI]  =  1.91, 2.10) took longer to stabilize than the control group (1.90 ± 0.07 seconds, 95% CI  =  1.86, 1.95) (F(1,22)  =  4.28, P  =  .05). This result was associated with a large effect size and a 95% CI that did not cross zero (Cohen d  =  1.0, 95% CI  =  0.91, 1.09). CONCLUSIONS: Although they were Division I female athletes at an average of 2.5 years after ACL reconstruction, participants with ACLR knees demonstrated dynamic postural-control deficits as evidenced by their difficulty in controlling ground reaction forces. This increased TTS measurement might contribute to the established literature reflecting differences in single-limb dynamic control. Clinicians might need to focus rehabilitation efforts on stabilization after jump landing. Further research is needed to determine if TTS is a contributing factor in future injury.